Implementasi Model AISAS dalam Penulisan Naskah Reels pada Instagram @pln.iconplus - Siti Ainun Arsy; Alfa Taufan Latif; Fikry Fachrurrizal (Lembaga Pengembangan Kinerja Dosen, 2026)
Fierce competition in digital marketing demands creativity in short-form video content. This study aims to analyze the implementation of the AISAS (Attention, Interest, Search, Action, Share) model in writing Instagram Reels scripts for the @pln.iconplus account, using a sample video titled